1999
DOI: 10.1038/46816
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2C is an EDHF synthase in coronary arteries

Abstract: In most arterial beds a significant endothelium-dependent dilation to various stimuli persists even after inhibition of nitric oxide synthase and cyclo-oxygenase. This dilator response is preceded by an endothelium-dependent hyperpolarization of vascular smooth muscle cells, which is sensitive to a combination of the calcium-dependent potassium-channel inhibitors charybdotoxin and apamin, and is assumed to be mediated by an unidentified endothelium-derived hyperpolarizing factor (EDHF). Here we show that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
510
3
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 830 publications
(535 citation statements)
references
References 19 publications
14
510
3
2
Order By: Relevance
“…Using a coronary vessel bioassay system, Gebremedhin et al [5]implicated a CYP450 metabolite as the mediator of the bradykinin-mediated activation of smooth muscle calcium-activated K + channels. Interestingly, transfection of porcine coronary arteries with a CYP2C8/34 antisense oligonucleotide decreased CYP2C protein levels and attenuated bradykinin-induced EDHF vasodilation [7]. Taken together, these studies provide strong evidence that a CYP450-derived epoxygenase metabolite is responsible for the EDHF component of the renal microvascular response to bradykinin.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Using a coronary vessel bioassay system, Gebremedhin et al [5]implicated a CYP450 metabolite as the mediator of the bradykinin-mediated activation of smooth muscle calcium-activated K + channels. Interestingly, transfection of porcine coronary arteries with a CYP2C8/34 antisense oligonucleotide decreased CYP2C protein levels and attenuated bradykinin-induced EDHF vasodilation [7]. Taken together, these studies provide strong evidence that a CYP450-derived epoxygenase metabolite is responsible for the EDHF component of the renal microvascular response to bradykinin.…”
Section: Discussionmentioning
confidence: 58%
“…Endothelium-derived EETs dilate blood vessels by activating vascular smooth muscle K + channels, resulting in membrane hyperpolarization [3, 4, 5]. Additionally, cytochrome P450 (CYP450) inhibitors and antisense oligonucleotides have been reported to block EDHF-mediated vasodilation in isolated blood vessels from several organs and species [4, 5, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…The biochemical nature of the inhibitory interaction between NO and EDHF remains to be elucidated in detail, but there is evidence to suggest that it may involve a cGMP-dependent mechanism. Alternatively, NO itself may inhibit cytochrome P-450 2C and, therefore, the release of EET, which has been described as an EDHF [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study by Fisslthaler et al [29]has shown that the induction of cytochrome P450 enzymes in native endothelial cells enhances EDHF-mediated relaxation and hyperpolarization to bradykinin. In addition, the report also demonstrated attenuated EDHF-mediated vascular responses in arteries transfected with cytochrome P450 antisense oligonucleotides [29].…”
Section: Discussionmentioning
confidence: 99%